Parental Expectations for International Schools in the Digital Age - Srisuda Namraksa; Tanpat Kraiwanit (Universal Journal of Educational Research)
This study aims to explain the expectations parents have in sending their children to study in international schools in Nonthaburi, Thailand, in terms of teaching and learning courses, management reputation, the building location, and the schools' adaptation to the digital age. A qualitative approach was employed as a research strategy. Purposive sampling was used in in-depth interviews. The data were analysed using content analysis. The results showed that parents have expectations in sending children to study in international schools in the digital age, in Nonthaburi, Thailand, in four aspects. For teaching and learning courses, parents expect that these courses will teach students to be creative and assertive. For the management reputation, parents expect that the school will have a good reputation with a quality of teaching that is reliable. They expect a good image of effective and clear management policies. For the building location, parents expect to have a safe building with sufficient facilities. For the adaptation to the digital age, parents expect that there will be lessons on how to use electronic devices and various online media. Children should be taught how to avoid dangers from using them. Children will get the opportunity to use modern technological equipment. This study may be beneficial to education business groups and international schools, which can use data from the research in planning, improving, or formulating business strategies, as well as developing the education system to adjust to improvements in technology and beyond.